Structure monitoring subsystem in system of complex technological systems - Zigunov, Alexander; Kyshenko, Vasil (My University, 2014)
The efficient managing of complex technological system can be greatly enhanced with the help of control scripts using. These models reflect the processes of changing in time of phase coordinates and object's functions conditions. The system fixes the transitions to a new qualitative state from managing point of view.
Keywords: структура підсистеми моніторингу; технологічні системи; моніторинг; структура подсистемы мониторинга; технологические системы; мониторинг; structure of monitoring subsystem; technological systems; monitoring; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка